Impact of a Novel Pretreatment on Bond Strength of Universal Adhesive to Conventional and CAD/CAM Resin Composites: In Vitro Study - Ali A. Elkaffas; Abdullah Alshehri; Feras Alhalabi; Rania Bayoumi; Abdullah Ali Alqahtani; Abdulellah Almudahi; Abdulaziz Fahd Alsubaie; Abdulaziz Fahd Alharbi (Journal of Functional Biomaterials)
Novel dentin bonding pretreatment using copper sulfate (CuSO4) and dipotassium hydrogen phosphate (K2HPO4) may create a more hydrophobic environment for dentin bonding. Thus, this study aims to investigate the impact of a CuSO4 + K2HPO4 pretreatment on dentin μTBS when bonded with a universal adhesive to conventional and CAD/CAM resin composites. Eighty recently extracted human molars (n = 80) were chosen and placed in transparent acrylic blocks to expose the crowns entirely. Nano-filled resin composite and CAD/CAM resin blocks were selected. Based on the dentin pretreatment, type of resin composite, and adhesion strategy, the teeth were randomly allocated into eight equal groups (n = 10). The microtensile bond strength (μTBS) and fracture mode were determined. A three-way analysis of variance (ANOVA) was used to analyze the μTBS data, followed by Tukey’s post hoc test. The μTBS values were not significantly affected by either the resin composite type (p > 0.05) or the adhesive strategy (p > 0.05) according to the three-way ANOVA results. Conversely, significant differences were detected between no dentin pretreatment (24.20 ± 4.54 MPa) and CuSO4 + K2HPO4 pretreatment (33.66 ± 5.22 MPa) using an etch-and-rinse adhesive strategy for nano-filled composites (p < 0.001). Additionally, significant differences were detected between no dentin pretreatment (24.71 ± 4.33 MPa) and CuSO4 + K2HPO4 pretreatment (32.49 ± 4.92 MPa) using an etch-and-rinse adhesive strategy for CAD/CAM resin blocks (p < 0.001). Moreover, significant differences were detected between no dentin pretreatment (21.20 ± 3.40 MPa) and CuSO4 + K2HPO4 pretreatment (30.31 ± 3.87 MPa) using a self-etching adhesive strategy for nano-filled composites (p < 0.001). Also, significant differences were detected between no dentin pretreatment (23.89 ± 3.89 MPa) and CuSO4 + K2HPO4 pretreatment (31.22 ± 4.71 MPa) using a self-etching adhesive strategy for CAD/CAM resin blocks (p < 0.001). In conclusion, dentin μTBS was enhanced by a copper-based treatment when used with nano-filled and CAD/CAM resin blocks.